The work of Francisco Raúl Carnese and his contribution to Argentine Biological Anthropology - Avena, Sergio (Instituto de Ciencias Antropológicas, Facultad de Filosofía y Letras, UBA, 2022)
Francisco Raúl Carnese has been a central figure in Argentine and Latin American Biological Anthropology. His contributions to the discipline are discussed, based on events of interest that have marked his career, both for his teaching and research activities. His activity was developed first in the School of Natural Sciences and Museum of the Universidad Nacional de La Plata and then in the School of Philosophy and Literatures of the Universidad de Buenos Aires, serving as dean in both institutions. He has been a pioneer in the aplication of population genetics in Argentine Anthropology, both in past and present populations, and in native and cosmopolitan peoples. The main objectives of his activity have been to question racial classifications and the myth of European Argentina, which aims to invisibilize not only the native american and Afro-descendant population, but also the very existence of admixture in our country.